KENDALA PEMERINTAH KOTA PEKANBARU DALAM MENGOPTIMALKAN PENERIMAAN PENDAPATAN DAERAH DARI PAJAK HOTEL TAHUN 2012- 2015(STUDI PADA DINAS PENDAPATAN DAERAH KOTA PEKANBARU) - ", Mawaddah; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Local Revenue constitutes acceptance of the tax levy, retribution, the result of a local company, the acceptance of the services and other receipts were included in the original income (PAD) is concerned, and is an area of legitimate income. In the management of local taxes, especially taxes in the city of Pekanbaru on the local regulation of Pekanbaru No. 7 of 2011 on Taxes Hotel where in article 1, paragraph 11 mentioned the hotel tax is a tax on the services provided by the hotel, then in chapter 12 also said that the object of taxation the hotel is a service provided by the hotel pambayaran, including services as a supplement to hotels that are giving kemudahann and comfort, including sports and entertainment facilities. And implementation of hotel tax collection was organized by the Regional Revenue Office Pekanbaru. The purpose of this study was to determine what factors are causing the decline in revenue (PAD) from the hotel tax in the city of Pekanbaru and to find out how the policies Regional Revenue Office Pekanbaru in increasing tax revenue through hotel in the city of Pekanbaru. This research uses descriptive research using qualitative approach. The results based on interviews and field observations note that the factors causing a decline in revenue (PAD) from the hotel tax in the city of Pekanbaru include a lack of enforcement of sanctions against taxpayers who do not pay kewajibnya, mental attitude, discipline, motivation is still low of Revenue employee Pekanbaru, Pekanbaru political situation is not conducive so that taxpayers tend to be cautious in paying his taxes, crisis of public confidence in the local government of Pekanbaru in managing local taxes and Awareness taxpayer in paying hotel taxes are still low. In order to increase the hotel tax receipts that the target can be achieved then the local government, especially the Department of Revenue has made an effort Pekanbaru expansion and intensification in the field of taxation. Extensification done by pemunggutan which has been implemented by the Regional Revenue Office Pekanbaru and intensification of the activities that are ongoing in barengi with existing tax management with the goal of increasing the tax object. Keywords: Taxes, Taxes, Regional Revenue Office Pekanbaru